Diseño y desarrollo de un selector automático de residuos reciclables (2019)
The main objective of this project was the creation of an Automatic selector of recyclable waste prototype that allows us to classify and recycle it in a correct way. In a previous analysis we could realize the needed of an efficient waste separation in Antonio Nariño University in order to contribute to the environment, taking into account that this waste is not manage correctly in the ecological points, for that reason low recycling rates have been found in the country. This problem affects all social environments, also, it generates environmental degradation and health problems. This project not only pretends the efficient waste separation; it also pretends to create a conscious mind about contamination and the correct manage of waste. For that reason, a prototype has been done in the process of technological investigation in order to identify and classify waste like plastic, paper and metal. On the first hand a use of sensors in the ecological points of the university has been determined in order to identify a sample of the most common waste. On the other hand, a system of automatic control has been designed in each one of the institutional containers. Finally, the implementation of the system with its respective tests is carried out and its effectiveness is established.